VERBAL DESCRIPTION OF THE TECHNOLOGY FOR PLANNING THE QUALITY IMPROVEMENT OF A SUBSET OF THE PROCESSES OF THE SPICE MATURITY REFERENCE MODEL - Godlevskyi, Mykhaylo; Burlakov, Georgii (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2023)
It is noted that to solve the problem of developing information technology for planning the increase of maturity level of a subset of the processes of the SPICE reference maturity model, this issue must first be considered at the verbal level as a technology (sequence of stages) for the implementation of the given problem. At the first stage, the structure of the SPICE reference model, which consists of a number of separate processes, was formalized. This set is presented as a hierarchical structure: the first level is a set of processes and subprocesses; the second level is a set of process groups; the third level is a set of process categories. At the second stage, the method of assessing the level of possibility of a separate process/sub-process of the reference maturity model SPICE is considered. It is given from the point of view of two dimensions of the SPICE model: the purpose of the processes; the attributes of the processes (measurable characteristics necessary for managing the process and increasing the possibility of its execution). The third stage of the technology is focused on the synthesis of planning model of the subset development processes for the SPICE model, which determines the quality level of a separate component of the software development process (SDP), which in turn has a positive effect on the level of development of software systems. Assessment and planning of the possibility level of a subset of processes is implemented during a certain planning period under conditions of limited resources based on their optimal distribution, taking into account the importance of individual processes and their practices during the planning period. At the fourth stage of the technology, an algorithm for planning the development of a subset of processes of the reference maturity model SPICE is considered based on the method of sequential analysis of options. This is primarily due to the fact that the optimization model has an additive objective function. The method allows discarding those appropriate solutions that do not contain optimal solutions. In the future, when specifying the model, it is planned to choose an algorithm that belongs to this method and adapt it to the solution of the given problem. The fifth stage is devoted to information technology implementation of the developed model and algorithm. At this stage, the following set of problems is solved. Analysis of business processes of the technology of improving the quality of software development process. Definition of software requirements. Forming a diagram of use cases. Development of data models. Justification of the choice of tools for software development. Selection of reference system architecture. Next, software coding and testing. At the sixth stage, based on information technology, a number of variants of the plan for improving the quality of a subset of the processes of the SPICE maturity model are formed in order to support decision-making by the management of the IT company. For this, a set of effective solutions is preliminarily determined, which is proposed to determine the final option, which is implemented later.